Effect of gravity on the pattern formation in aqueous suspensions of luminous Escherichia coli - Boleslovas Dapkūnas; Romas Baronas; Remigijus Šimkus (Nonlinear Analysis)
This paper presents a nonlinear two-dimensional-in-space mathematical model of self-organization of aqueous bacterial suspensions. The reaction–diffusion–chemotaxis model is coupled with the incompressible Navier–Stokes equations, which are subject to a gravitational force proportional to the relative bacteria density and include a cut-off mechanism. The bacterial pattern formation of luminous Escherichia coli is modelled near the inner lateral surface of a circular microcontainer, as detected by bioluminescence imaging. The simulated plume-like patterns are analysed to determine the values of the dimensionless model parameters, the Schmidt number, Rayleigh number and oxygen cut-off threshold, that closely match the patterns observed experimentally in a luminous E. coli colony. The numerical simulation at the transient conditions was carried out using the finite difference technique.